Biochemical and Virulence Characterization of Vibrio vulnificus Isolates From Clinical and Environmental Sources - Lydon, Keri A.; Kinsey, Thomas; Le, Chinh; Gulig, Paul A.; Jones, Jessica L. (Frontiers in Cellular and Infection Microbiology, 2021)
Vibrio vulnificus is a deadly human pathogen for which infections occur via seafood consumption (foodborne) or direct contact with wounds. Virulence is not fully characterized for this organism; however, there is evidence of biochemical and genotypic correlations with virulence potential. In this study, biochemical profiles and virulence genotype, based on 16S rRNA gene (rrn) and virulence correlated gene (vcg) types, were determined for 30 clinical and 39 oyster isolates. Oyster isolates were more biochemically diverse than the clinical isolates, with 4 of the 20 tests producing variable (defined as 20-80% of isolates) results. Whereas, for clinical isolates only mannitol fermentation, which has previously been associated with virulence potential, varied among the isolates. Nearly half (43%) of clinical isolates were the more virulent genotype (rrnB/vcgC); this trend was consistent when only looking at clinical isolates from blood. The majority (64%) of oyster isolates were the less virulent genotype (rrnA or AB/vcgE). These data were used to select a sub-set of 27 isolates for virulence testing with a subcutaneously inoculated, iron-dextran treated mouse model. Based on the mouse model data, 11 isolates were nonlethal, whereas 16 isolates were lethal, indicating a potential for human infection. Within the nonlethal group there were eight oyster and three clinical isolates. Six of the nonlethal isolates were the less virulent genotype (rrnA/vcgE or rrnAB/vcgE) and two were rrnB/vcgC with the remaining two of mixed genotype (rrnAB/vcgC and rrnB/vcgE). Of the lethal isolates, 5 were oyster and 11 were clinical. Eight of the lethal isolates were the less virulent genotype and seven the more virulent genotype, with the remaining isolate a mixed genotype (rrnA/vcgC). A discordance between virulence genotype and individual mouse virulence parameters (liver infection, skin infection, skin lesion score, and body temperature) was observed; the only variable associated with mouse virulence parameters was season (warm or cold conditions at time of strain isolation), with more virulent strains isolated from cold conditions. These results indicate that biochemical profiles and genotype are not significantly associated with virulence potential, as determined by a mouse model. However, a relationship with virulence potential and seasonality was observed.